Do ESG Matter for Investor in ASEAN-5? Evidence from Mining and Property Companies - Ervina Rahmalia Putri; Erfan Muhammad; Tito IM. Rahman Hakim; Frida Fanani Rohma (Jurnal Akuntansi dan Keuangan, 2026)
ESG disclosures constitute vital non-financial communication channels that potentially influence investor perceptions and capital deployment strategies, consequently affecting firm value. Audit committee oversight within governance architectures is theorized to amplify the value-generating capacity of ESG programs, especially in environmentally impactful industries including mining and property sectors. This study analyzes firms spanning five Southeast Asian markets during 2021-2023. ESG, as a whole, harms firm value across the mining and property sector in ASEAN-5. Audit committee characteristics demonstrate insufficient moderating influence on ESG-firm value relationships. By performing additional tests, environmental and governance indicators exhibit favorable correlations with firm value, whereas social metrics display negligible statistical significance. Empirical findings demonstrate heterogeneous effects for composite ESG and its pillars on firm value. Results indicate that some notions of legitimacy and agency theory are not advocated. Investors need to remain vigilant in digesting ESG information from the mining and property companies in ASEAN-5 countries, as its composite and pillars affect firm value in distinct ways. The government could codify the rule to mandate a sustainability committee to ensure ESG information credibility for all high-risk environmental sectors, especially in ASEAN-5.